Perfecting pregnancy : law, disability, and the future of reproduction - Karpin, Isabel; Savell, Kristin, 1968- (Cambridge : Cambridge University Press, 2012)
'Prenatal and preimplantation testing technologies have offered unprecedented access to information about the genetic and congenital makeup of our prospective progeny. Future developments such as preconception testing, non-intrusive prenatal testing and more extensive preimplantation testing promise to increase that access further still. The result may be greater reproductive choice, but it also increases the burden on women and men to avail themselves of these technologies in order to avoid having a child with a disability. The overwhelming question for legislators has been whether and, if so, how to regulate the use of these technologies in the face of compelling but seemingly contradictory claims about the advancement of reproductive choice and the dangers of eugenic or discriminatory effects. This book examines the evolution of this legislative oversight across a number of jurisdictions and explores the tensions and ambiguities that inform these laws'--
Machine generated contents note: 1. Disability; 2. Risk; 3. Terminations; 4. De-selections; 5. Interpretations; 6. Futures.
Includes bibliographical references (pages 349-373) and index.
Keywords: Human reproduction -- Law and legislation; Pregnancy -- Law and legislation; Pregnant women -- Legal status, laws, etc